Employee Engagement and Organizational Performance of Nepalese Financial Sector - Prasad Devkota, Sruya; Rai, Bharat; Bhakta Sharma, Bhanu (Nepal Journal of Multidisciplinary Research, 2025)
Background: A company's success depends on its human resources, and strategies like hiring, training, and empowerment are crucial for raising output and performance. Although empowerment has been associated with favorable results like increased engagement and decreased employee turnover, its impact on organizational performance is still debatable; other research points to problems like inadequate oversight. In order to provide useful insights for management strategies, this study aims to investigate the impact of employee engagement on performance in Nepalese public enterprises—an area that has received little attention. Purpose: Examining the connection between organizational performance and employee engagement in Nepalese public companies is the goal of this study. The study aims to provide light on how engagement tactics might enhance organizational results and direct management practices in Nepal going forward by examining important engagement variables. Design and Methodology: Data was gathered from 600 employees of different public firms in Nepal using a survey methodology. Cronbach's Alpha was used to evaluate the measurement tools' dependability; the results showed consistency with a value of 0.758. Findings: According to the study, organizational success and employee engagement are significantly positively correlated. The significance of the top three engagement indicators was highlighted by the fact that they explained over 80% of performance variation and 86.7% of engagement variation. Higher levels of enthusiasm and drive were displayed by employees with less education and shorter tenure, even if employee engagement was mostly unchanged by gender, education, and work experience. While they struggled to achieve; technological development and research productivity, organizations excelled in community impact, staff retention, and service quality. These results highlight the necessity for firms to prioritize motivation, involvement, and innovation by reaffirming the connection between improved performance and increased engagement. Conclusion: The study emphasizes how closely organizational performance and employee engagement are related. The reliability of the tools is confirmed by reliability analysis, which yielded a Cronbach's Alpha of 0.758. Over 80% of the variance in employee engagement and performance may be explained by the primary components identified by Principal Component Analysis (PCA). According to descriptive statistics, engagement is stable across many demographic groupings, with higher levels of engagement shown among employees with shorter tenure and lesser qualifications. According to regression research, employee engagement and performance are positively correlated, indicating that raising employee engagement can improve performance as a whole. To promote performance improvements, organizations should give engagement initiatives top priority, especially in research and innovation. Practical implication: For Public Enterprises seeking to boost productivity, this paper offers insightful information. Emphasizing employee engagement—achievable through greater motivation, involvement, and creativity—allows businesses to improve outcomes like service quality and staff retention. Additionally, it highlights the importance of customized engagement strategies that address the needs of various staff groups, particularly those with different tenure and educational backgrounds. Furthermore, encouraging innovation and establishing inclusive work cultures are essential to maintaining a competitive advantage in the market and ensuring consistent performance across a range of demographics. Novelty of the study This study is distinctive because it emphasizes the vital role that employee engagement plays in boosting organizational performance while concentrating on the particular circumstances of Nepalese public companies. By highlighting customized tactics like workforce diversity, empowerment, and a focus on workers with shorter job tenures to improve productivity and service quality, it provides useful insights for both enterprises and governments.